Fecundación asistida y consentimiento informado: ¿qué tan informado es dicho consentimiento? - Cárdenas Krenz, Arturo Ronald (2015)
This article is about the risks for health that could be caused by the in vitro fertilization, a topic that it is not much spread in our society, nevertheless it is a matter of special importance to talk about a real informed assent.